2017
DOI: 10.3389/feart.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Potential for Low-Level Transport of Black Carbon Emissions from Cropland Burning in Russia to the Snow-Covered Arctic

Abstract: Short lived aerosols and pollutants transported from northern mid-latitudes have amplified the short term warming in the Arctic region. Among those black carbon is recognized as the second most important human emission in regards to climate forcing, behind carbon dioxide, with a total climate forcing of +1.1 Wm −2 . Studies have suggested that cropland burning may be a large contributor to the black carbon emissions which are directly deposited on the snow in the Arctic. However, commonly applied atmospheric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Note that, as shown by Konovalov et al (2015Konovalov et al ( , 2017a, the atmospheric evolution of aerosol originating from Russian boreal fires may be much more strongly affected by aerosol aging processes involving both primary and secondary semi-volatile organic compounds than represented in the CHIMERE simulations using the standard SOA scheme. Note also that, although experimental findings (Hand et al, 2010) suggest that fresh BB aerosol particles originating from forest fires are composed of predominantly hydrophobic material, aerosol aging processes are likely to increase the hygroscopicity of aerosol particles containing BC and to accelerate their removal from the atmosphere by precipitation through in-cloud scavenging (Stier et al, 2006;Oshima et al, 2012;Paramonov et al, 2013). However, these shortcomings of our simulations are not likely to lead to any significant biases in our estimates of BC emissions, as evidenced by the sensitivity tests discussed in Sect.…”
Section: Chimere Model Simulationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Note that, as shown by Konovalov et al (2015Konovalov et al ( , 2017a, the atmospheric evolution of aerosol originating from Russian boreal fires may be much more strongly affected by aerosol aging processes involving both primary and secondary semi-volatile organic compounds than represented in the CHIMERE simulations using the standard SOA scheme. Note also that, although experimental findings (Hand et al, 2010) suggest that fresh BB aerosol particles originating from forest fires are composed of predominantly hydrophobic material, aerosol aging processes are likely to increase the hygroscopicity of aerosol particles containing BC and to accelerate their removal from the atmosphere by precipitation through in-cloud scavenging (Stier et al, 2006;Oshima et al, 2012;Paramonov et al, 2013). However, these shortcomings of our simulations are not likely to lead to any significant biases in our estimates of BC emissions, as evidenced by the sensitivity tests discussed in Sect.…”
Section: Chimere Model Simulationsmentioning
confidence: 86%
“…Several studies (e.g., Shindell and Faluvegi, 2009;Flanner, 2013;Sand et al, 2015) have indicated that a significant part (up to about 50 %) of this temperature increase could have been induced by BC. There is an abundant amount of evidence that BB provides a significant contribution to BC in the Arctic atmosphere in the spring and summer (e.g., Stohl, 2006;Stohl et al, 2006;Warneke et al, 2010;Bian et al, 2013;Hall and Loboda, 2017;Popovicheva et al, 2017;Winiger et al, 2017;Qi et al, 2017;Xu et al, 2017;Evangeliou et al, 2018). It has also been estimated that Siberian fires alone contributed almost half (46 %) of the total BC amount deposited in the Arctic over a period of 12 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013).…”
Section: Introductionmentioning
confidence: 99%
“…Her notable works include the development of new algorithms for determining burned area and carbon cycle products in satellite sensor imagery [34] and assessing fire risk in Russia [243]. Her recent works have included efforts to assess black carbon emissions from cropland burning in Russia, with impacts on the Arctic [244,245].…”
Section: Approachmentioning
confidence: 99%
“…Her notable works include the development of new algorithms for determining burned area and carbon-cycle products in satellite sensor imagery [200], and assessing fire risk in Russia [412]. Her recent works include efforts to assess black carbon emissions from cropland burning in Russia, with impacts on the Arctic [413,414].…”
Section: Kendra Mclauchlan Is a Professor At Kansas State University mentioning
confidence: 99%